PENGARUH BIAYA PRODUKSI TERHADAP HARGA PENJUALAN BUBUK TEH PADA PT. PERKEBUNAN NUSANTARA IV TOBASARI SIDAMANIK DENGAN METODE REGRESI LINEAR BERGANDA - Uni Fiana Silalahi; Arnah . Ritonga (Universitas Negeri Medan, 2017)
ABSTRACT In the electric power system operation required an electrical load forecasting. The method used to forecast electrical load, one of which is a method of linear Regresi(berganda logic). In this research, short-term load forecasting electricity, namely electric load forecasting for the category weekdays, Saturdays, Sundays at the time of peak load on the electrical system Sumbagut. The structure of the regresi variables used are historical load, temperature, and load forecaster to determine the value of each parameter and regersion sets of each of the variables and model parameter values to the fuzzification process with linear representation up, down, and triangles. After that designing reasoning rules to get assertive value of each rule based on membership degree obtained and change the value, the weighted average method centered. Keywords: Regresion linear metodet berganda.